Evaluasi Tata Kelola Teknologi Informasi pada PT Telkom Data Ekosistem (NeutraDC) Menggunakan Framework COBIT 2019 Domain APO - Balqis, Fika Halimah; Hasbi Aufa Ibrahim; Nur Aeni Hidayah (JSI: Jurnal Sistem Informasi (E-Journal), 2025)
This study evaluated information technology governance at PT Telkom Data Ekosistem (NeutraDC), a subsidiary of Telkom Indonesia operating in the data center services industry. As a key player in Indonesia’s digital transformation, NeutraDC was expected to ensure effective management of information and data security. The study focused on evaluating governance capabilities in two areas of COBIT 2019: APO13 (Managed Security) and APO14 (Managed Data). The main issues addressed were the absence of a formal assessment of existing capabilities and the lack of improvement benchmarks. A quantitative descriptive methodology was applied, involving questionnaires and interviews with information technology staff, and analyzed using the six-level COBIT capability model. The results showed that both areas achieved Level 5 (Optimizing), indicating the presence of strong policies, continuous monitoring, and proactive risk management. These findings reflected a mature and robust information technology governance process. However, the study recommended continuous improvement through regular audits, training, and policy updates to keep pace with technological and regulatory developments. The study provided actionable insights for organizations seeking to strengthen their data governance and information security through a unified framework.